Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Keputusan Pembelian Pada Es Krim Wall’s di Sidoarjo Kota - Boggy Nugraha Pramana; Ugy Soebiantoro (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The research entitled The Effect of Product Quality and Price Perception on Purchase Decisions at Wall's Ice Cream in Sidoarjo City was conducted with the aim of knowing the effect of Product Quality (X1) and Price Perception (X2) on Purchase Decisions (Y) Wall's Ice Cream in Sidoarjo City. The population in this study are consumers who buy Wall's ice cream in Sidoarjo and use a sample that are consumers who have bought Wall's ice cream products in stalls, minimarkets, supermarkets, and hypermarkets located in Sidoarjo city (within 2 months since the questionnaire was distributed) with 126 respondents. person. This study uses a quantitative approach with the analytical technique used in this study is partial least square (PLS) and sampling using purposive sampling technique and using primary data through questionnaires. The test results obtained in this study are product quality has an influence on purchasing decisions and price perceptions also have an influence on purchasing decisions so that both variables are stated to be true that have an influence on purchasing decisions. Keywords: Buying Decision ; Price Perception ; Product Quality